Emerging Economy Business Cycles : Financial Integration and Terms of Trade Shocks - Bhattacharya, Rudrani (IMF Working Papers; Working Paper ;, 2013)
This paper analyses the extent to which financial integration impacts the manner in which terms of trade affect business cycles in emerging economies. Using a s mall open economy model, we show that as capital account openness increases in an economy that faces trade shocks, business cycle volatility reduces. For an economy with limited financial openness, and a relatively open trade account, a model with exogenous terms of trade shocks is able to replicate the features of the business cycle.